Differences in Nutritional Intake and Upper Arm Circumference (UAC) Between Anemic and Normal Pregnant Women - Erlinawati Lubis; Fitri Apriyanti; Elvira Harmia; Nislawaty Nislawaty (Window of Health : Jurnal Kesehatan, 2026)
Anemia is an indirect cause of maternal mortality, with a 27.7% prevalence among pregnant women in Indonesia, including rising cases in Riau and Kampar. It increases the risk of hemorrhage, low birth weight, preterm birth, stunting, and maternal and infant mortality, influenced by inadequate nutrition and low mid-upper arm circumference. The purpose of this study was to analyze the differences in nutritional intake and upper arm circumference (UAC) between pregnant women with anemia and pregnant women without anemia. The method in this research is a comparative, observational, analytical study of two unpaired groups with a cross-sectional design. The population consisted of pregnant women with anemia and normal pregnant women in the working area of the Salo Community Health Center, Kampar District, totaling 74 samples (37 per group). The study was conducted in August-September 2025. The data collection tools used were a UAC tape, an SQ-FFQ for nutritional intake, and a digital hemoglobinometer to measure anemia. Bivariate analysis was performed using an independent samples t-test. The results show that pregnant women with anemia had lower nutritional intake scores and smaller mean UAC compared to non-anemic pregnant women. Statistical analysis confirmed significant differences between the two groups in nutritional intake (p = 0.012) and UAC (p = 0.028), with both p-values below the significance level of α 0.05. Pregnant women with anemia have lower nutritional intake and UAC, highlighting the need to improve maternal nutrition and use UAC monitoring for early anemia screening.